Auricular acupressure combined with auricular acupoint massage enhances cognitive function in night shift nurses: a P300 wave analysis - Li, Xiaoqin; Zhang, Zhun; Xiao, Litian; Zhang, Xuan; Yao, Huiqi; Li, Fangqin; Chen, Rongyu; Zhong, Qian (Frontiers in Human Neuroscience, 2025)
ObjectivesNight-shift work is associated with cognitive impairments, but convenient, effective, and acceptable traditional Chinese medicine-based interventions remain limited. This study aimed to evaluate the effects of auricular acupressure combined with auricular acupoint massage on cognitive function in night-shift nurses, using P300 wave parameters from electroencephalography analysis as objective metrics.MethodsEighty nurses (40 days-shift, 40 night-shift) participated. The intervention included auricular acupressure and massage targeting six points, performed daily for 4 weeks. Cognitive function was assessed using the Insomnia Severity Index (ISI), Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE). P300 amplitude and latency were measured.ResultsNight-shift nurses had significantly higher ISI scores and lower MoCA attention, memory, and total scores compared to day-shift nurses (all p < 0.05). Before the intervention, After FDR correction for multiple comparisons, P300 amplitude was significantly lower at the T4 electrode site (q = 0.020) in the night-shift group. P300 latency remained significantly prolonged at sites Fz (q = 0.020), F3 (q < 0.001), F4 (q = 0.035), and T5 (q = 0.033). Post-intervention, the night-shift group demonstrated significant increases in P300 amplitude at F3, F4, T3, T4, T5, and T6 (all q < 0.05) and significant reductions in P300 latency at Fz, F4, F7, T5, and T6 (all q < 0.05). Notably, several sites with affected P300 amplitude and latency before the intervention showed significant improvement following intervention.ConclusionAuricular acupressure and massage significantly improved cognitive function in night-shift nurses, evidenced by enhanced P300 parameters. This non-invasive, cost-effective intervention shows promise for alleviating cognitive impairments from shift work.